1998
DOI: 10.1093/jac/42.1.103
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and toxicity of once-daily tobramycin therapy in children with cystic fibrosis

Abstract: The pharmacokinetics and toxicity of once-daily intravenous tobramycin were studied prospectively in seven children with cystic fibrosis. Mean 1 h post-dose concentrations of 21.9 mg/L (S.D. 3.0) and 40.2 mg/L (S.D. 8.1) were achieved following tobramycin doses of 8 mg/kg and 15 mg/kg, respectively. The half-life (mean 2.3 h) was unchanged at the two doses, as were the total clearance and volume of distribution. All patients responded well to therapy. No nephrotoxicity occurred, but one patient showed transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 9 publications
6
36
1
Order By: Relevance
“…Four studies reported at least one episode of ototoxicity, with a frequency of 8-14%. 45,49,53,55 In one study the side effect was not clinically significant55; the other three studies did not comment on clinical significance. 45,49,53 The overall frequency of ototoxicity in the eight studies was 3.5% (9/254), with it occurring in 4.1% (7/171) and 2.4% (2/83) of patients treated with ODD and traditional regimen, respectively.…”
Section: Ototoxicitymentioning
confidence: 94%
See 3 more Smart Citations
“…Four studies reported at least one episode of ototoxicity, with a frequency of 8-14%. 45,49,53,55 In one study the side effect was not clinically significant55; the other three studies did not comment on clinical significance. 45,49,53 The overall frequency of ototoxicity in the eight studies was 3.5% (9/254), with it occurring in 4.1% (7/171) and 2.4% (2/83) of patients treated with ODD and traditional regimen, respectively.…”
Section: Ototoxicitymentioning
confidence: 94%
“…6,11,[44][45][46][47][48][49][50][51][52][53][54][55][56] This regimen also was investigated in neonates up to 1 month of age but is not discussed here due to the decreased renal function in that patient population. Infectious processes included neutropenic fever, suspected or confirmed gramnegative infections, cystic fibrosis, and suspected or confirmed surgical infections.…”
Section: Efficacy In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…day -1 of tobramycin [102] and netilmicin [120] has been associated with symptoms of dizziness after the antibiotic infusion. However, surprisingly few side-effects have been reported in high dose aminoglycoside therapy [89,121,122]. Nevertheless, it is necessary to monitor ototoxicity and renal function and adjust the dosage interval accordingly, early in therapy [64].…”
Section: Intravenous Antipseudomonal Antibiotic Therapy In Cystic Fibmentioning
confidence: 99%